Modulation of the interleukin-6 signalling pathway and incidence rates of atherosclerotic events and all-cause mortality: analyses from the Canakinumab Anti-Inflammatory Thrombosis Outcomes Study (CANTOS). (26th August 2018) - Ridker, Paul M; Libby, Peter; MacFadyen, Jean G; Thuren, Tom; Ballantyne, Christie; Fonseca, Francisco; Koenig, Wolfgang; Shimokawa, Hiroaki; Everett, Brendan M; Glynn, Robert J
Abstract: Aims: Canakinumab, a monoclonal antibody targeting interleukin (IL)-1β, reduces rates of recurrent cardiovascular events without lowering lipids. It is uncertain, however, to what extent these beneficial cardiovascular outcomes are mediated through interleukin-6 (IL-6) signalling, an issue with substantial pathophysiologic consequences and therapeutic implications. Methods and results: A total of 4833 stable atherosclerosis patients in the Canakinumab Anti-Inflammatory Thrombosis Outcomes Study (CANTOS) had IL-6 levels measured before randomization and after treatment with placebo or one of three doses of canakinumab (50 mg, 150 mg, or 300 mg) given subcutaneously once every 3 months. Participants were followed for up to 5 years (median follow-up 3.7 years). Compared with those allocated to placebo, CANTOS participants receiving canakinumab who achieved on-treatment IL-6 levels below the study median value of 1.65 ng/L experienced a 32% reduction in major adverse cardiovascular events [MACE, multivariable adjusted hazard ratio (HR adj ) 0.68, 95% confidence interval (CI) 0.56–0.82; P < 0.0001], a 30% reduction in MACE plus the additional endpoint of hospitalization for unstable angina requiring urgent revascularization (MACE+, HR adj 0.70, 95% CI 0.59–0.84; P < 0.0001), a 52% reduction in cardiovascular mortality (HR adj 0.48, 95% CI 0.34–0.68; P < 0.0001), and a 48% reduction in all-cause mortality (HR adj 0.52, 95% CI 0.40–0.68; P < 0.0001) with prolonged treatment. In contrast, those with on-treatment IL-6 levels equal to or above 1.65 ng/L after taking the first dose of canakinumab had no significant benefit for any of these endpoints. These differential findings based on the magnitude of IL-6 response were seen in analyses alternatively based on tertiles of on-treatment IL-6 levels, and in analyses using a statistical inference approach to estimate the effect of treatment among individuals who would achieve a targeted IL-6 level. Conclusion: CANTOS provides proof of concept evidence in humans that modulation of the IL-6 signalling pathway, at least with canakinumab, associates with reduced cardiovascular event rates, independent of lipid lowering. Clinical trial registration: ClinicalTrials.gov NCT01327846.